Sliding Mode Observer and Event Triggering Mechanism Co-design - Amara, H. E.; Latreche, S.; Sid, M. A.; Khemliche, M. (Engineering, Technology & Applied Science Research, 2020)
Sliding mode observer and event triggering mechanism co-design is the subject of this paper. The synthesis of a sliding mode observer under any event triggering mechanism is given, where the proposed observer can be viewed as a special structure of the Kalman filter. Then, the event triggering condition is updated according to the coverage index value computed with the help of the reachability set representation. A numerical example illustrates the effectiveness of the proposed approach.